KEPENTINGAN EKONOMI POLITIK INDONESIA DIKAWASAN AMERIKA LATIN DALAM ORGANISASI INTRA REGIONAL FEALAC (Forum for East Asia Latin America Cooperation) - Liana Fitri; Indra Pahlawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research illustrates the political economy of Indonesia in East Asia LatinAmerican countries. The focus of this study was to determine the interests of the Indonesianpolitical economy in Latin America, which is the subject and the main goal within theframework of intra regional organization FEALAC. Latin American countries that aremembers of FEALAC is a promising partnership in the sector import-export, FEALAC alsoa forum with a huge potential to increase intra regional cooperation. Targets to be achievedby is made FEALAC as a means to enhance mutual understanding, strengthen politicaldialogue, develop cooperation, as well as forming new partnerships and strategic betweenEast Asia and Latin America.This study, using data collected from books, journals, massa media and websites ofinterest to analyze the Indonesian economy in the Latin American intra regionalorganization FEALAC. The theory used in this study the theory of the political economy ofIndonesia from Donald E. Necterlain, Defence Interest, Economic interest, Word OrderInterest, Interest ideological. Economic interests even become one of the points used in theIndonesian cooperation with the member countries of the Latin America region FEALAC.Explores the opinions for effective execution and sustainability of FEALAC. As anon-traditional markets, Latin America is still considered a potential market for Indonesia.Identification of potential countries as a partner that will be a priority Indonesian nontraditionalmarkets in Latin America would be something relevant in international tradecooperation program in Indonesia.Keyword: Economy and Political Cooperation, FEALAC, Interests of Indonesian, Nontraditional Markets